Quality Of Services Jaringan Wireless Di SMKS Yapim Mandau - Era Yohana Oktaviani Silalahi; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Wireless network is a wireless network that uses air as a transmission medium with the medium in the form of electromagnetic waves. Yapim Mandau-Duri Vocational School, is a private vocational school with its address at Jalan thorn kilometer 8. Yapim Mandau-Duri Vocational School currently uses an internet network in the form of a wireless network, where the wireless network at Yapim Mandau-Duri Vocational School uses two access points. at SMK Yapim Mandau-Duri, the distance and speed of signal coverage can be disrupted due to several factors, such as the transmission range that is not too far away and obstacles in the form of thick walls that hinder signal transmission at SMK Yapim Mandau-Duri. Duri High School. To determine the quality of the existing network at SMK Yapim Mandau-Duri, it is necessary to measure the quality of the network using the Quality Of Services (QoS) parameter, QoS is a method of measuring how good the service quality of the existing network is, the parameter used is Throughput. In this study the average throughput for 5 clients for 5 days starting from the first test to the fifth day. The highest average Throughput for 5 days occurred to the fifth user at 174 Kbps, and the lowest average Throughput value occurred to the second user at 149 Kbps. The average Throughput obtained was very good according to TIPHON standards. The quality of TIPHON serves to determine qualifications in measuring the quality of the internet network. Keyword: Wireless, Access Point, Parameter QoS, Throughput, TIPHON Standard.